Effect of sleeper bottom texture on lateral resistance with discrete element modelling. (30th July 2020) - Guo, Yunlong; Fu, Hao; Qian, Yu; Markine, Valeri; Jing, Guoqing
Highlights: Innovated sleeper shape with texture attached at sleeper bottom. Comparison of different friction sleeper design. Discrete element modelling of sleeper-ballast interaction. A rapid method for discrete element method model construction. Abstract: The lateral stability of ballasted track becomes more important because of the safety requirement under the demand of higher train speed and heavier axle load. To increase the lateral resistance of ballast bed, this paper proposes three types of new sleepers, frictional sleepers. The frictional sleepers are sleepers with different shapes of textures attached at the sleeper bottom. To study the application feasibility of the frictional sleepers, experimental tests (single sleeper pull-out test) and numerical simulation (discrete element modelling) are performed. The lateral resistances of the three types of frictional sleepers are compared with the traditional sleeper based on the experimental test, and the mechanism of the lateral resistance increase is revealed according to the numerical simulation. The results indicate that the frictional sleepers can increase the lateral resistance by 32% (maximum), due to the enhanced interaction between sleeper and ballast particles. More importantly, different types of frictional sleepers have different performances, and the optimal friction sleeper is confirmed. This study is helpful for the further research on sleeper design.